2021
DOI: 10.5334/irsp.452
|View full text |Cite
|
Sign up to set email alerts
|

A More Competent, Warm, Feminine, and Human Leader: Perceptions and Effectiveness of Democratic Versus Authoritarian Political Leaders

Abstract: Nowadays, to the detriment of democratic leaders, the emergence of authoritarian leaders has drastically modified the political sphere. This project aims to shed light on this issue by analysing how the perceived effectiveness of democratic and authoritarian political leaders are shaped by the common dimensions of social perception, such as competence/warmth, masculinity/femininity, and human uniqueness/human nature. Accordingly, three experimental studies were conducted. In Study 1 (n = 1001), we revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This might imply that warmth and assigned gender do not seem to influence trust, helpfulness and competence in ways that were anticipated based on the stereotypeliterature such as SCM and agency communion (Awale et al 2019;Brambilla et al 2011;Caprariello et al 2009;Conway et al 1996Cuddy et al 2009DeFranza et al 2020;Fiske et al 2002;Fiske 2018;Kevryn et al 2013;Kurt et al 2011;Nejat et al 2020;Sainz et al 2021), and literature on how stereotypes are transferred to AI applications (Costa and Ribas 2019;Nowak and Fox 2018) which was surprising as the expectation of differences were grounded in a large quantity of literature. Based on the SCM model, the study should have shown differences in outcomes after exposure to both warmth and assigned gender, both because they evoke stereotypical responses as variations of warmth is related to expectations of gender, however the K current study did not live up to these expectations as no such differences or responses were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might imply that warmth and assigned gender do not seem to influence trust, helpfulness and competence in ways that were anticipated based on the stereotypeliterature such as SCM and agency communion (Awale et al 2019;Brambilla et al 2011;Caprariello et al 2009;Conway et al 1996Cuddy et al 2009DeFranza et al 2020;Fiske et al 2002;Fiske 2018;Kevryn et al 2013;Kurt et al 2011;Nejat et al 2020;Sainz et al 2021), and literature on how stereotypes are transferred to AI applications (Costa and Ribas 2019;Nowak and Fox 2018) which was surprising as the expectation of differences were grounded in a large quantity of literature. Based on the SCM model, the study should have shown differences in outcomes after exposure to both warmth and assigned gender, both because they evoke stereotypical responses as variations of warmth is related to expectations of gender, however the K current study did not live up to these expectations as no such differences or responses were found.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the effect of chatbot's assigned gender and gendered language on trust, perceived helpfulness, and perceived competence the current study draws on knowledge from social perception theories such as agency-communion and SCM as they create an interesting yet useful lens to look at the relationship through. In the vast majority of social cognition and perception theories and literature two dimensions appear, namely warmth-communion and competence-agency dimensions (Sainz et al 2021), based in agency-communion literature and SCM literature. It has been demonstrated that these dimensions occur across regions and cultures (Cuddy et al 2009;DeFranza et al 2020;Durante et al 2017).…”
Section: Human-machine Communication Through a Social Perceptions Lensmentioning
confidence: 99%